Report for "American Birds" Midwestern Prarie Region: 1 August - 30 November 1976 - DeCoster, Richet al (1976)
Report for "American Birds" Midwestern Prarie Region" contributed by Rich DeCoster. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of Fall 1976. Epson - sheet feed/flatbed